Ultrasonic-assisted variable speed loading extrusion infiltration method for preparing ceramic-metal dual continuous gradient composite materials

By using ultrasonic assisted variable speed loading technology in the extrusion impregnation process of ceramic metal double continuous gradient composite materials, the inadequate filling and defects caused by the pore size gradient of porous ceramic prefabricated bodies are solved, and more efficient impregnation filling and materials are achieved Performance improvement.

CN118385541BActive Publication Date: 2024-12-20HARBIN INST OF TECH AT WEIHAI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410496184.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-23
Publication Date
2024-12-20
Estimated Expiration
2044-04-23

AI Technical Summary

Technical Problem

In the extrusion and impregnation process of ceramic metal double continuous gradient composite materials, the alloy melt is insufficiently filled due to the change in the pore size gradient of the porous ceramic preform, which easily leads to turbulence, air wrapping and defects, and is difficult to wet, resulting in the performance of composite materials. reduce.

Method used

Using ultrasonic assisted variable speed loading extrusion and impregnation method, the loading rate is reduced by applying longitudinal ultrasonic vibration and gradient variable speed loading on the porous ceramic prefabricated body, and the loading rate is established, and the impregnation pressure gradient is suitable for multi-scale pore size structures is promoted to promote the melt flow network. The formation of the impregnation filling effect is improved and defects are avoided.

Benefits of technology

The overall impregnation saturation of ceramic metal double continuous gradient composite materials is improved, defects such as shrinkage, loosening and interfacial cracks are avoided, and the mechanical properties of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118385541B_ABST
    Figure CN118385541B_ABST
Patent Text Reader

Abstract

The present application relates to the field of preparation of ceramic-metal composite materials, and specifically to an ultrasonic-assisted variable speed loading extrusion infiltration method for preparing ceramic-metal dual-continuous gradient composite materials, comprising the following steps: preparing a porous ceramic preform; melting the pre-impregnated alloy to obtain a molten alloy; preheating an ultrasonic vibration-variable speed loading mold, preheating the ceramic preform, and placing the porous ceramic preform into the ultrasonic vibration-variable speed loading mold; pouring the molten alloy into the ultrasonic vibration-variable speed loading mold; applying ultrasonic vibration to the bottom of the ultrasonic vibration-variable speed loading mold; applying pressure on the punch of the ultrasonic vibration-variable speed loading mold and implementing variable speed loading; taking out after the infiltration is completed and cooling to room temperature to obtain a ceramic-metal dual-continuous gradient composite material. The preparation method of the present application can realize the rapid preparation of ceramic-metal dual-continuous gradient composite materials in an atmospheric environment without protective gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of preparation of ceramic-metal composite materials, and in particular to an ultrasonically assisted variable speed loading extrusion infiltration method for preparing ceramic-metal dual-continuous gradient composite materials. Background Art

[0002] Ceramic-metal dual-continuous gradient composites have changed the layered combination and discrete layered gradient structure of traditional composites. There is no macroscopic interface inside. The ceramic content decreases gradually and the metal content increases along the incoming surface. The performance gradient changes relieve stress concentration, reduce the interface reflection tensile wave and transverse shear wave intensity, and improve the anti-penetration performance and anti-multiple strike capabilities. Among them, the liquid metal infiltration process is currently one of the mainstream methods for preparing ceramic-metal dual-continuous gradient composites, and the extrusion infiltration process has significant advantages in preparing high-density and large-size gradient composites due to its fewer production processes, high efficiency, and wide material applicability.

[0003] At present, due to the gradient porous structure of porous ceramic preforms, the following problems exist in the preparation of ceramic-metal dual-continuous gradient composites by extrusion infiltration: the porous ceramic preform with pore size gradient change has an extremely complex structure, and its pore size gradient change structure will cause insufficient filling of the alloy melt. Under conventional constant speed loading conditions, the molten alloy flows faster in the large-scale interlayer pores with reduced gradient, which is prone to turbulence, air entrapment and other phenomena. In the small-scale intralayer pores, the melt flow, solidification and shrinkage behaviors are extremely uneven. The large deformation resistance of the first solidified area restricts the mechanical shrinkage effect, which is prone to defects and even un-infiltrated areas. At the same time, the extrusion infiltration forming of difficult-to-wet ceramic-metal composites requires a large infiltration pressure to break the oxide film on the surface of the liquid metal and overcome the capillary resistance between the micropores of the preform, which is very easy to cause partial or overall damage to the preform during the preparation process, thereby reducing the performance of the composite material.

[0004] Therefore, the current preparation method of ceramic-metal dual-continuous gradient composites still needs to be improved so that the ceramic-metal dual-continuous gradient composites can be prepared quickly. Summary of the invention

[0005] The purpose of the present application is to provide an ultrasonically assisted variable speed loading extrusion infiltration method for preparing a ceramic-metal dual continuous gradient composite material.

[0006] The embodiments of the present application can be implemented through the following technical solutions:

[0007] An ultrasonic-assisted variable speed loading extrusion infiltration method for preparing a ceramic-metal dual continuous gradient composite material comprises the following steps:

[0008] Step 1, preparing a porous ceramic preform;

[0009] Step 2, melting the pre-impregnation alloy to obtain a molten alloy;

[0010] Step 3, preheating the ultrasonic vibration-variable speed loading mold to a preset temperature, preheating the porous ceramic preform to a preset temperature, and placing the porous ceramic preform into the ultrasonic vibration-variable speed loading mold;

[0011] Step 4, pouring the molten alloy into the ultrasonic vibration-variable speed loading mold until the porous ceramic preform is completely covered;

[0012] Step 5, applying ultrasonic vibration to the bottom of the ultrasonic vibration-variable speed loading mold;

[0013] Step six, applying pressure on the punch of the ultrasonic vibration-variable speed loading mold;

[0014] Step 7, performing variable speed loading on the punch of the ultrasonic vibration-variable speed loading die;

[0015] Step eight, after the infiltration is completed, the composite material is taken out from the ultrasonic vibration-variable speed loading mold and cooled to room temperature to obtain a ceramic-metal bicontinuous gradient composite material.

[0016] Furthermore, the ceramic preform in step one has a pore size gradient change, the volume fraction of the porous ceramic preform continuously changes gradiently between 15vol% and 70vol% along the thickness direction, the pore size of the interlayer pores continuously changes gradiently between 20 and 120μm, the interlayer pores include large interlayer pores and small interlayer pores, and the pore size of the intralayer pores continuously changes gradiently between 1 and 10μm.

[0017] Furthermore, the raw material for preparing the porous ceramic preform in step 1 is ZrB 2 Ceramics, ZrC ceramics, ZrO 2 Ceramics, SiC ceramics, Si 3 N 4 Ceramics, B 4 C ceramics, Al 2 O 3 Ceramic, TiB 2 One or a combination of ceramics.

[0018] Furthermore, the pre-impregnation alloy in step 2 is any one of cemented carbides.

[0019] Furthermore, the preset temperature of the ultrasonic vibration-variable speed loading mold in step three is 500-550°C.

[0020] Furthermore, the preset temperature of the porous ceramic preform in step three is 500-550°C.

[0021] Furthermore, in step five, the ultrasonic power is 1000-2000w, the amplitude is 0.1-100μm, the ultrasonic action time is 100-1000s, and the ultrasonic frequency is 15-30kHz.

[0022] Furthermore, in step six, the pressure applied on the punch of the ultrasonic vibration-variable speed loading mold is 20 to 40 MPa.

[0023] Furthermore, the variable speed loading method in step seven is gradient variable speed loading. When filling large pores between layers, the loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 5-7 mm / s. When filling small pores between layers, the loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 3-4 mm / s. When filling pores within the layer, the loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 1-2 mm / s.

[0024] Furthermore, when the continuous variable speed loading is implemented in step seven, within a preset time, the loading speed of the punch of the ultrasonic vibration-variable speed loading die is continuously and uniformly reduced between 5 and 1 mm / s.

[0025] An ultrasonically assisted variable speed loading extrusion infiltration method for preparing a ceramic-metal dual continuous gradient composite material provided in an embodiment of the present application has at least the following beneficial effects:

[0026] 1. In the present application, the infiltration of molten alloy into a porous ceramic preform with a pore size gradient is promoted by using an extrusion infiltration method with variable speed loading. The infiltration pressure gradient adapted to the gradient change of the multi-scale pore size structure is established by reducing the loading rate, promoting the formation of a melt flow network and local shrinkage compensation in the micropores in the small-sized ceramic layer, improving the stability of the molten alloy flow front in the large-sized interlayer pores, avoiding the generation of defects such as shrinkage cavities, looseness, and interface cracks, and improving the overall infiltration saturation of the composite material;

[0027] 2. The variable speed loading extrusion infiltration in the present application can improve the flow behavior of the alloy melt in the porous ceramic preform with pore size gradient change by reducing the loading rate, realize laminar stable filling, and eliminate the influence of pore size and its gradient change on the flow of the alloy melt by forming a flow network of the alloy melt;

[0028] 3. In the present application, the ultrasonic efficiency is improved by applying longitudinal ultrasonic vibration in the same direction as the pore size of the porous ceramic preform with a pore size gradient change, thereby improving the dynamic wettability of the melt to the porous ceramic preform, thereby promoting the infiltration and filling of the porous ceramic preform with the molten alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1This is a process flow chart of ultrasonic-assisted variable speed loading extrusion infiltration preparation of the ceramic-metal dual continuous gradient composite material of the present application;

[0030] Figure 2 B of Example 1 in this application 4 Scanning electron microscope image of C / 2024Al dual continuous gradient composite material;

[0031] Figure 3 This is a reference diagram for the ultrasonic-assisted variable speed loading extrusion infiltration preparation process for the ceramic-metal dual continuous gradient composite material of the present application. DETAILED DESCRIPTION

[0032] Hereinafter, the present application will be further described based on preferred embodiments with reference to the accompanying drawings.

[0033] In addition, various components on the drawings are enlarged (thickened) or reduced (thinned) for ease of understanding, but this practice is not intended to limit the scope of protection of the present application.

[0034] Words importing the singular also include the plural and vice versa.

[0035] In the description of the embodiments of the present application, it should be noted that if the terms "upper", "lower", "inside", "outside", etc. indicate an orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, or the orientation or positional relationship in which the products of the embodiments of the present application are usually placed when in use, it is only for the convenience of describing the present application and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. In addition, in the description of the present application, in order to distinguish different units, the words first, second, etc. are used in this specification, but these are not limited by the order of manufacture, nor can they be understood as indicating or implying relative importance, and their names may be different in the detailed description and claims of the present application.

[0036] The vocabulary in this specification is used to illustrate the embodiments of the present application, but is not intended to limit the present application. It should also be noted that, unless otherwise clearly specified and limited, the terms "disposed", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, a direct connection, an indirect connection through an intermediate medium, or a connection between the two elements. For those skilled in the art, the specific meanings of the above terms in this application can be specifically understood.

[0037] The present application provides an ultrasonic-assisted variable speed loading extrusion infiltration method for preparing a ceramic-metal dual continuous gradient composite material. Figure 1The ultrasonic-assisted variable speed loading extrusion infiltration preparation process flow chart for preparing ceramic-metal dual continuous gradient composite materials in this application is shown as follows: Figure 1 As shown, the preparation method comprises the following steps:

[0038] Step 1, preparing a porous ceramic preform with a pore size gradient change, wherein the volume fraction of the porous ceramic preform changes continuously and gradually between 15 vol% and 70 vol% along the thickness direction, the pore size of the interlayer pores changes continuously and gradually between 20 and 120 μm, the interlayer pores include interlayer macropores with a pore size of 50 to 120 μm and interlayer micropores with a pore size of 20 to 50 μm, and the pore size of the intralayer pores changes continuously and gradually between 1 and 10 μm, and at the same time, the raw material for preparing the porous ceramic preform is ZrB 2 Ceramics, ZrC ceramics, ZrO 2 Ceramics, SiC ceramics, Si 3 N 4 Ceramics, B 4 C ceramics, Al 2 O 3 Ceramic, TiB 2 One or a combination of ceramics.

[0039] Step 2, melting the pre-impregnation alloy to obtain a molten alloy, wherein the pre-impregnation alloy is one of hard alloys such as Al alloy and Ti alloy;

[0040] Step 3, preheating the ultrasonic vibration-variable speed loading mold to a preset temperature of 500-550° C., preheating the porous ceramic preform obtained in step 1 to a preset temperature of 500-550° C., and placing the porous ceramic preform into the ultrasonic vibration-variable speed loading mold;

[0041] Step 4, pouring the molten alloy into the ultrasonic vibration-variable speed loading mold until the porous ceramic preform is completely covered;

[0042] Step 5, continuously applying longitudinal ultrasonic vibration to the bottom of the ultrasonic vibration-variable speed loading mold, the ultrasonic power is 1000-2000w, the amplitude is 0.1-100μm, the ultrasonic action time is 100-1000s, and the ultrasonic frequency is 15-30kHz;

[0043] Furthermore, for cemented carbide materials, in order to ensure that the stress on the loading surface is uniform during the loading process, a spring-type flexible loading method can be adopted, that is, an ultrasonic vibration longitudinal flexible loading device is designed on the ejection structure of the ultrasonic vibration-variable speed loading mold, and four springs are used to flexibly connect the ultrasonic tool head and the top plate of the device. While achieving balanced force on the same plane, longitudinal ultrasonic waves consistent with the aperture direction of the preform are applied to establish conditions for acoustic capillary and strong acoustic cavitation.

[0044] Step six, applying pressure on the punch of the ultrasonic vibration-variable speed loading mold, the pressure being 20 to 40 MPa;

[0045] Step 7, performing gradient variable speed loading or continuous variable speed loading on the punch of the ultrasonic vibration-variable speed loading die;

[0046] Specifically, when implementing gradient speed-changing loading, firstly, a scanning electron microscope is used to observe the microstructure of the porous ceramic preform in step 1, and the lengths of the interlayer macropores and interlayer micropores, as well as the volume fraction of the porous ceramic preform within the length range are determined. At the same time, the downward stroke of the punch of the ultrasonic vibration-speed-changing loading die in the interlayer macropores and the interlayer micropores is the product of the extent of the interlayer macropores and the length of the interlayer micropores and the porosity within the length range, respectively.

[0047] Furthermore, when filling the large pores between layers, the loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 5-7 mm / s. After the large pores between layers are infiltrated and filled, the small pores between layers are further filled, and the loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 3-4 mm / s. After the small pores between layers are infiltrated and filled, the pores within the layers are further filled, and the loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 1-2 mm / s, until the infiltration is completed.

[0048] Specifically, when continuously variable speed loading is implemented, within a preset time, the loading speed of the punch of the ultrasonic vibration-variable speed loading die is continuously and uniformly reduced between 5 and 1 mm / s through the loading parameters of the servo press.

[0049] Step eight, after the infiltration is completed, the composite material is taken out from the ultrasonic vibration-variable speed loading mold and cooled to room temperature, and finally a ceramic-metal bicontinuous gradient composite material is obtained.

[0050] The present application provides an ultrasonic-assisted variable-speed loading extrusion infiltration method for preparing a ceramic-metal bicontinuous gradient composite material, wherein longitudinal ultrasonic vibration is applied while the molten alloy is infiltrated into a porous ceramic preform with a pore size gradient change. The strong acoustic cavitation effect generated by the molten alloy under the action of longitudinal ultrasonic excitation is essentially a series of dynamic processes formed by the tiny bubbles existing inside the liquid being subjected to the action of a periodic alternating sound field under the action of ultrasonic waves. In the negative pressure stage of the sound wave, the bubbles are stretched and grow to form cavitation bubbles; in the positive pressure stage, the cavitation bubbles close rapidly. Due to the extremely fast closing speed, the cavitation bubbles collapse and generate huge instantaneous high pressure and instantaneous high temperature. This process is called cavitation, which can quickly destroy and eliminate the newly generated oxide film on the surface of the molten alloy, ensuring the contact between the molten alloy and the porous ceramic preform with a pore size gradient change. At the same time, the microjets generated in the viscous boundary layer around the bubbles also promote the mass transfer process in the liquid, causing the microbubbles to grow continuously. The bubbles that have grown up will condense under the action of force, and then move to the surface of the melt under the action of buoyancy. As the bubble wall loses its surface tension, it will break and enter the atmosphere, thus achieving the effect of degassing. Acoustic streaming is the non-periodic motion caused by the propagation of strong sound waves in gas or liquid media.

[0051] When ultrasonic waves propagate in liquid media, due to the absorption and attenuation effects of sound waves, a sound pressure change with a certain gradient will be formed from the sound source to the propagation direction, which will cause the liquid medium to flow, and when the sound pressure amplitude increases to a certain value, a fluid jet will be generated in the medium. These phenomena are called the acoustic streaming effect of ultrasonic waves. Although the speed of acoustic streaming is much lower than the particle vibration speed in the propagation medium, it can also reach more than 5 times the thermal convection speed inside the fluid, thereby further promoting the wetting and infiltration of the porous ceramic preform with a pore size gradient by the molten alloy, and ensuring the integrity of the porous ceramic preform by reducing the infiltration pressure. The pressure pulse generated when the cavitation bubble collapses can form a directional rush flow, exerting a force on the end face of the molten alloy in the capillary, causing the molten alloy to rise in height, that is, the acoustic capillary effect. The lamellar gaps in the porous ceramic preform with a pore size gradient and the small aperture pores in the lamella form countless capillary-like channel structures. Therefore, the acoustic capillary effect can promote the spontaneous filling of the molten alloy into the gaps of the porous ceramic preform with a pore size gradient.

[0052] By reducing the loading rate, an infiltration pressure gradient adapted to the gradient change of the multi-scale pore structure is established. Since the interlayer pores of the porous ceramic preform are relatively large at the initial stage of extrusion infiltration, a faster extrusion infiltration speed is adopted to ensure that the molten alloy is effectively filled without premature solidification; as the pore size decreases, the infiltration resistance will increase, the local flow rate will accelerate, turbulence, air entrapment and insufficient infiltration will occur, and continuous infiltration of the melt will become difficult. At this time, the extrusion infiltration speed is reduced to ensure that the melt at the infiltration front flows stably while having enough time to fully fill the small-sized interlayer pores in the porous ceramic preform; since the porous ceramic preform has 2-5μm intralayer microvoids as a whole, after the molten alloy has completed the filling of the large-sized interlayer microvoids, the extrusion infiltration speed is further reduced to ensure that the intralayer microvoids are fully filled while ensuring the integrity of the porous ceramic preform.

[0053] The porous ceramic preform in the present application has the characteristic of gradient change of pore structure. After the liquid metal enters the porous ceramic preform, the molten alloy will not solidify at the same time. Volume shrinkage usually occurs during the cooling process of the liquid metal. During this period, the fluid pressure and gas pressure change dynamically. The gas is discharged from the solidification zone and enters the liquid in the unsolidified zone, causing the gas pressure to increase and the fluid pressure to decrease. When the gas pressure is equal to the fluid pressure, pores may be formed. If such pores are not fully compensated, shrinkage and loose defects will result. The variable speed loading strategy is adopted. On the one hand, it promotes the formation of melt flow network and local shrinkage compensation in the micropores of small-sized ceramic layers. The alloy melt flows in a network-like form, which is conducive to fully filling the micropores in the small-sized ceramic layers. On the other hand, it improves the stability of the flow front of the molten alloy in the large-sized interlayer pores. By reducing the loading rate, the flow behavior of the molten alloy in the porous ceramic preform with a pore size gradient change is improved to achieve laminar stable filling, that is, the molten alloy has an adaptive flow rate when flowing into pore structures of different scales, so that the streamlines are parallel and do not cross, thereby improving the overall infiltration saturation of the composite material. By optimizing the loading conditions, the pressure is transmitted to the entire molten alloy through the inner wall of the mold or the solidified shell that has undergone plastic deformation, so that the solidification temperature of all the molten alloys is increased at the same time under the same action, and the fluidity of the molten alloy is further enhanced, which is conducive to avoiding the occurrence of shrinkage cavities and looseness.

[0054] The ultrasonic vibration-variable speed loading extrusion infiltration forming process realizes the wetting and infiltration of the difficult-to-wet alloy melt into the ceramic preform in the preparation process, and the effective infiltration of the pores with gradient changes in multi-scale pore structure through the acoustic-mechanical-thermal multi-field coupling, while ensuring the integrity of the porous ceramic preform; the strong acoustic cavitation and acoustic capillary action inside the micropores are used to improve the wettability between the melt and the ceramic, and the acoustic streaming effect can accelerate the escape of residual gas in the pores of the porous ceramic preform, thereby promoting the smooth progress of the infiltration; the variable speed loading technology is used to improve the flow behavior of the molten alloy in the porous ceramic preform with gradient changes in multi-scale pore structure by reducing the loading rate, to achieve laminar stable filling, and to eliminate the influence of pore scale and its gradient change on the flow of the molten alloy with the help of the formation of the molten alloy flow network.

[0055] Embodiment 1

[0056] The present application provides an ultrasonic-assisted variable speed loading extrusion infiltration method for preparing a ceramic-metal dual continuous gradient composite material, the preparation method comprising the following steps:

[0057] Step 1: Prepare B with pore size gradient by freeze drying-high temperature sintering method 4 C porous ceramic preform, B 4 The volume fraction of the C porous ceramic preform changes continuously and gradually between 15 vol% and 50 vol% along the thickness direction, the pore size of the interlayer pores changes continuously and gradually between 20 and 80 μm, the interlayer pores include interlayer macropores and interlayer micropores, and the pore size of the intralayer pores changes continuously and gradually between 1 and 6 μm.

[0058] Step 2, melting the pre-impregnated 2024 aluminum alloy to obtain a molten 2024 aluminum alloy;

[0059] Step 3: preheat the ultrasonic vibration-variable speed loading mold to 500°C, and 4 The porous ceramic preform C is preheated to 500°C and the B 4 C. The porous ceramic preform is placed in the ultrasonic vibration-variable speed loading mold;

[0060] Step 4: pouring the molten 2024 aluminum alloy into the ultrasonic vibration-variable speed loading mold until the B 4 C porous ceramic preform;

[0061] Step 5, continuously applying longitudinal ultrasonic vibration to the bottom of the ultrasonic vibration-variable speed loading mold, the ultrasonic power is 1000w, the amplitude is 0.1μm, the ultrasonic action time is 100s, and the ultrasonic frequency is 15kHz;

[0062] Step six, applying a pressure of 20 MPa on the punch of the ultrasonic vibration-variable speed loading mold;

[0063] Step seven, implementing gradient variable speed loading on the punch of the ultrasonic vibration-variable speed loading mold. When filling the large pores between layers, the loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 5 mm / s. After the large pores between layers are infiltrated and filled, the small pores between layers are further filled. The loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 3 mm / s. After the small pores between layers are infiltrated and filled, the pores within the layer are further filled. The loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 1 mm / s until the infiltration is completed.

[0064] Step 8: After the impregnation is completed, the mixture is taken out from the ultrasonic vibration-variable speed loading mold and cooled to room temperature to finally obtain B 4 C / 2024Al dual continuous gradient composite material.

[0065] Figure 2 For B 4 Scanning electron microscope image of C / 2024Al double continuous gradient composite material, such as Figure 2 As shown in the figure, the dark color is 2024 aluminum alloy and the light color is B 4 C porous ceramic preform. It can be seen from the figure that the porous ceramic preform and the molten alloy are tightly combined without obvious cracks and holes, indicating that under this process, the molten alloy can well infiltrate and fill the ceramic blank skeleton. At the same time, through mechanical property testing, B 4 The compressive strength of C / 2024Al dual-continuous gradient composite is 802MPa and the fracture toughness is 9.8MPa·m 1 / 2 , the flexural strength is 541MPa. 4 From the microstructure of the C / 2024Al dual-continuous gradient composite material, it can be seen that there are no obvious defects such as large-sized holes or microcracks inside the material, the bonding interface between the ceramic phase and the alloy phase is clean and the bonding is good, and the overall structure of the composite material is dense.

[0066] Embodiment 2

[0067] The present application provides an ultrasonic-assisted variable speed loading extrusion infiltration method for preparing a ceramic-metal dual continuous gradient composite material, the preparation method comprising the following steps:

[0068] Step 1: Prepare B with pore size gradient by freeze drying-high temperature sintering method 4 C porous ceramic preform, B 4The volume fraction of the C porous ceramic preform changes continuously and gradually between 30 vol% and 70 vol% along the thickness direction, the pore size of the interlayer pores changes continuously and gradually between 40 and 120 μm, the interlayer pores include interlayer macropores and interlayer micropores, and the pore size of the intralayer pores changes continuously and gradually between 2 and 10 μm.

[0069] Step 2, melting the pre-impregnated 2024 aluminum alloy to obtain a molten 2024 aluminum alloy;

[0070] Step 3: preheat the ultrasonic vibration-variable speed loading mold to 550°C, and 4 The porous ceramic preform C is preheated to 550°C and the B 4 C. The porous ceramic preform is placed in the ultrasonic vibration-variable speed loading mold;

[0071] Step 4: pouring the molten 2024 aluminum alloy into the ultrasonic vibration-variable speed loading mold until the B 4 C porous ceramic preform;

[0072] Step 5, continuously applying longitudinal ultrasonic vibration to the bottom of the ultrasonic vibration-variable speed loading mold, the ultrasonic power is 2000w, the amplitude is 100μm, the ultrasonic action time is 1000s, and the ultrasonic frequency is 30kHz;

[0073] Step six, applying a pressure of 40 MPa on the punch of the ultrasonic vibration-variable speed loading mold;

[0074] Step seven, implementing gradient variable speed loading on the punch of the ultrasonic vibration-variable speed loading mold. When filling the large pores between layers, the loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 7 mm / s. After the large pores between layers are infiltrated and filled, the small pores between layers are further filled. The loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 4 mm / s. After the small pores between layers are infiltrated and filled, the pores within the layer are further filled. The loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 2 mm / s until the infiltration is completed.

[0075] Step 8: After the impregnation is completed, the mixture is taken out from the ultrasonic vibration-variable speed loading mold and cooled to room temperature to finally obtain B 4 C / 2024Al dual continuous gradient composite material.

[0076] After mechanical properties test, B 4 The compressive strength of C / 2024Al dual-continuous gradient composite is 841MPa and the fracture toughness is 9.1MPa·m 1 / 2 , the flexural strength is 492MPa. 4From the microstructure of the C / 2024Al dual-continuous gradient composite material, it can be seen that there are no obvious defects such as large-sized holes or microcracks inside the material, the bonding interface between the ceramic phase and the alloy phase is clean and the bonding is good, and the overall structure of the composite material is dense.

[0077] Embodiment 3

[0078] The present application provides an ultrasonic-assisted variable speed loading extrusion infiltration method for preparing a ceramic-metal dual continuous gradient composite material, the preparation method comprising the following steps:

[0079] Step 1: Prepare B with pore size gradient by freeze drying-high temperature sintering method 4 C porous ceramic preform, B 4 The volume fraction of the C porous ceramic preform varies continuously between 20 vol% and 60 vol% along the thickness direction, the pore size of the interlayer pores varies continuously between 20 and 100 μm, the interlayer pores include interlayer macropores and interlayer micropores, and the pore size of the intralayer pores varies continuously between 2 and 5 μm.

[0080] Step 2, melting the pre-impregnated 2024 aluminum alloy to obtain a molten 2024 aluminum alloy;

[0081] Step 3: preheat the ultrasonic vibration-variable speed loading mold to 520°C, and 4 The porous ceramic preform C is preheated to 520°C and the B 4 C. The porous ceramic preform is placed in the ultrasonic vibration-variable speed loading mold;

[0082] Step 4: pouring the molten 2024 aluminum alloy into the ultrasonic vibration-variable speed loading mold until the B 4 C porous ceramic preform;

[0083] Step 5, continuously applying longitudinal ultrasonic vibration to the bottom of the ultrasonic vibration-variable speed loading mold, the ultrasonic power is 2000w, the amplitude is 50μm, the ultrasonic action time is 300s, and the ultrasonic frequency is 20kHz;

[0084] Step six, applying a pressure of 30 MPa on the punch of the ultrasonic vibration-variable speed loading mold;

[0085] Step seven, implementing gradient variable speed loading on the punch of the ultrasonic vibration-variable speed loading mold. When filling the large pores between layers, the loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 6 mm / s. After the large pores between layers are infiltrated and filled, the small pores between layers are further filled. The loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 3 mm / s. After the small pores between layers are infiltrated and filled, the pores within the layer are further filled. The loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 1 mm / s until the infiltration is completed.

[0086] Step 8: After the impregnation is completed, the mixture is taken out from the ultrasonic vibration-variable speed loading mold and cooled to room temperature to finally obtain B 4 C / 2024Al dual continuous gradient composite material.

[0087] After mechanical properties test, B 4 The compressive strength of C / 2024Al dual-continuous gradient composite is 837MPa and the fracture toughness is 9.6MPa·m 1 / 2 , the flexural strength is 532MPa. 4 From the microstructure of the C / 2024Al dual-continuous gradient composite material, it can be seen that there are no obvious defects such as large-sized holes or microcracks inside the material, the bonding interface between the ceramic phase and the alloy phase is clean and the bonding is good, and the overall structure of the composite material is dense.

[0088] Embodiment 4

[0089] The present application provides an ultrasonic-assisted variable speed loading extrusion infiltration method for preparing a ceramic-metal dual continuous gradient composite material, the preparation method comprising the following steps:

[0090] Step 1: Prepare B with pore size gradient by freeze drying-high temperature sintering method 4 C porous ceramic preform, B 4 The volume fraction of the C porous ceramic preform varies continuously between 20 vol% and 60 vol% along the thickness direction, the pore size of the interlayer pores varies continuously between 20 and 100 μm, the interlayer pores include interlayer macropores and interlayer micropores, and the pore size of the intralayer pores varies continuously between 2 and 5 μm.

[0091] Step 2, melting the pre-impregnated 2024 aluminum alloy to obtain a molten 2024 aluminum alloy;

[0092] Step 3: preheat the ultrasonic vibration-variable speed loading mold to 520°C, and 4 The porous ceramic preform C is preheated to 520°C and the B 4 C. The porous ceramic preform is placed in the ultrasonic vibration-variable speed loading mold;

[0093] Step 4: pouring the molten 2024 aluminum alloy into the ultrasonic vibration-variable speed loading mold until the B 4 C porous ceramic preform;

[0094] Step 5, continuously applying longitudinal ultrasonic vibration to the bottom of the ultrasonic vibration-variable speed loading mold, the ultrasonic power is 2000w, the amplitude is 50μm, the ultrasonic action time is 300s, and the ultrasonic frequency is 20kHz;

[0095] Step six, applying a pressure of 30 MPa on the punch of the ultrasonic vibration-variable speed loading mold;

[0096] Step seven, implement continuous variable speed loading on the punch of the ultrasonic vibration-variable speed loading mold. Within 10 seconds, the loading speed of the punch of the ultrasonic vibration-variable speed loading mold is continuously and uniformly reduced between 5 and 1 mm / s through the loading parameters of the servo press. After completing the continuous variable speed loading, maintain the pressure for 20 seconds.

[0097] Step 8: After the impregnation is completed, the mixture is taken out from the ultrasonic vibration-variable speed loading mold and cooled to room temperature to finally obtain B 4 C / 2024Al dual continuous gradient composite material.

[0098] After mechanical properties test, B 4 The compressive strength of the C / 2024Al dual-continuous gradient composite is 847 MPa, which fully demonstrates the good performance of the composite under compressive load, and the fracture toughness is 10.4 MPa·m 1 / 2 , the flexural strength is 544MPa, and at the same time, it further improves the composite material to have good performance under complex stress state. 4 From the microstructure of the C / 2024Al dual-continuous gradient composite material, it can be seen that there are no obvious defects such as large-sized holes or microcracks inside the material. The bonding interface between the ceramic phase and the alloy phase is clean and the bonding is good. The overall structure of the composite material is dense, making it a new high-performance material with broad application prospects.

[0099] Embodiment 5

[0100] The present application provides an ultrasonic-assisted variable speed loading extrusion infiltration method for preparing a ceramic-metal dual continuous gradient composite material, the preparation method comprising the following steps:

[0101] Step 1: Prepare B with pore size gradient by freeze drying-high temperature sintering method 4 C porous ceramic preform, B 4The volume fraction of the C porous ceramic preform varies continuously between 20 vol% and 60 vol% along the thickness direction, the pore size of the interlayer pores varies continuously between 20 and 100 μm, the interlayer pores include interlayer macropores and interlayer micropores, and the pore size of the intralayer pores varies continuously between 2 and 5 μm.

[0102] Step 2, melting the pre-impregnated 2024 aluminum alloy to obtain a molten 2024 aluminum alloy;

[0103] Step 3: preheat the ultrasonic vibration-variable speed loading mold to 520°C, and 4 The porous ceramic preform C is preheated to 520°C and the B 4 C. The porous ceramic preform is placed in the ultrasonic vibration-variable speed loading mold;

[0104] Step 4: pouring the molten 2024 aluminum alloy into the ultrasonic vibration-variable speed loading mold until the B 4 C porous ceramic preform;

[0105] Step 5, continuously applying longitudinal ultrasonic vibration to the bottom of the ultrasonic vibration-variable speed loading mold, the ultrasonic power is 2000w, the amplitude is 50μm, the ultrasonic action time is 300s, and the ultrasonic frequency is 20kHz;

[0106] Step six, applying a pressure of 20 MPa on the punch of the ultrasonic vibration-variable speed loading mold;

[0107] Step seven, implementing gradient variable speed loading on the punch of the ultrasonic vibration-variable speed loading mold. When filling the large pores between layers, the loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 5 mm / s. After the large pores between layers are infiltrated and filled, the small pores between layers are further filled. The loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 4 mm / s. After the small pores between layers are infiltrated and filled, the pores within the layer are further filled. The loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 2 mm / s until the infiltration is completed.

[0108] Step 8: After the impregnation is completed, the mixture is taken out from the ultrasonic vibration-variable speed loading mold and cooled to room temperature to finally obtain B 4 C / 2024Al dual continuous gradient composite material.

[0109] After mechanical properties test, B 4 The compressive strength of C / 2024Al dual-continuous gradient composite is 813MPa and the fracture toughness is 9.3MPa·m 1 / 2 , the flexural strength is 519MPa. 4From the microstructure of the C / 2024Al dual-continuous gradient composite material, it can be seen that there are no obvious defects such as large-sized holes or microcracks inside the material, the bonding interface between the ceramic phase and the alloy phase is clean and the bonding is good, and the overall structure of the composite material is dense.

[0110] The above is a detailed introduction to the specific implementation methods of the present application. For those skilled in the art, several improvements and modifications may be made to the present application without departing from the principles of the present application. These improvements and modifications also fall within the scope of protection of the claims of the present application.

Claims

1. An ultrasonic-assisted variable speed loading extrusion infiltration method for preparing ceramic-metal dual continuous gradient composite materials, characterized in that: The following steps are involved: Step 1, preparing a porous ceramic preform with a pore size gradient change; Step 2, melting the pre-impregnation alloy to obtain a molten alloy; Step 3, preheating the ultrasonic vibration-variable speed loading mold to a preset temperature, preheating the porous ceramic preform to a preset temperature, and placing the porous ceramic preform into the ultrasonic vibration-variable speed loading mold; Step 4, pouring the molten alloy into the ultrasonic vibration-variable speed loading mold until the porous ceramic preform is completely covered; Step 5, applying ultrasonic vibration to the bottom of the ultrasonic vibration-variable speed loading mold; Step six, applying pressure on the punch of the ultrasonic vibration-variable speed loading mold; Step 7, performing variable speed loading on the punch of the ultrasonic vibration-variable speed loading die; Step eight, after the infiltration is completed, the composite material is taken out from the ultrasonic vibration-variable speed loading mold and cooled to room temperature to obtain a ceramic-metal bicontinuous gradient composite material.

2. The ultrasonic-assisted variable speed loading extrusion infiltration method for preparing ceramic-metal dual continuous gradient composite materials according to claim 1, characterized in that: The ceramic preform in step one has a pore size gradient change, the volume fraction of the porous ceramic preform changes continuously gradiently between 15vol% and 70vol% along the thickness direction, the pore size of the interlayer pores changes continuously gradiently between 20 and 120μm, the interlayer pores include interlayer large pores and interlayer small pores, and the pore size of the intralayer pores changes continuously gradiently between 1 and 10μm.

3. The ultrasonic-assisted variable speed loading extrusion infiltration method for preparing ceramic-metal dual continuous gradient composite materials according to claim 1, characterized in that: The raw material for preparing the porous ceramic preform in step 1 is one or a combination of ZrB2 ceramic, ZrC ceramic, ZrO2 ceramic, SiC ceramic, Si3N4 ceramic, B4C ceramic, Al2O3 ceramic, and TiB2 ceramic.

4. The ultrasonic-assisted variable speed loading extrusion infiltration method for preparing ceramic-metal dual continuous gradient composite materials according to claim 1, characterized in that: The pre-impregnation alloy in step 2 is any one of cemented carbides.

5. The ultrasonic-assisted variable speed loading extrusion infiltration method for preparing ceramic-metal dual continuous gradient composite materials according to claim 1, characterized in that: The preset temperature of the ultrasonic vibration-variable speed loading mold in step 3 is 500-550°C.

6. The ultrasonic-assisted variable speed loading extrusion infiltration method for preparing ceramic-metal dual continuous gradient composite materials according to claim 1, characterized in that: The preset temperature of the porous ceramic preform in step 3 is 500-550°C.

7. The ultrasonic-assisted variable speed loading extrusion infiltration method for preparing ceramic-metal dual continuous gradient composite materials according to claim 1, characterized in that: In step five, the ultrasonic power is 1000~2000w, the amplitude is 0.1~100µm, the ultrasonic action time is 100~1000s, and the ultrasonic frequency is 15~30kHz.

8. The ultrasonic-assisted variable speed loading extrusion infiltration method for preparing ceramic-metal dual continuous gradient composite materials according to claim 1, characterized in that: In step six, a pressure of 20-40 MPa is applied to the punch of the ultrasonic vibration-variable speed loading mold.

9. The ultrasonic-assisted variable speed loading extrusion infiltration method for preparing ceramic-metal dual continuous gradient composite materials according to claim 2, characterized in that: The variable speed loading method in step seven is gradient variable speed loading. When filling large pores between layers, the loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 5~7mm / s. When filling small pores between layers, the loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 3~4mm / s. When filling pores within the layer, the loading speed of the punch of the ultrasonic vibration-variable speed loading mold is 1~2mm / s.

10. The ultrasonic-assisted variable speed loading extrusion infiltration method for preparing ceramic-metal dual continuous gradient composite materials according to claim 1, characterized in that: When the continuous variable speed loading is implemented in step seven, within a preset time, the loading speed of the punch of the ultrasonic vibration-variable speed loading die is continuously and uniformly reduced between 5 and 1 mm / s.